Tongue Olympiad for the deaf a linguistic and educational experience - Zambrano Steensma, Ludmilan (2019)
In Venezuela, deaf people have the recognition of the Venezuelan Sign Language (LSV) that constitutes them as a minority linguistic community. Research on productions in LSV and the relationship of deaf people with oral and written Spanish, have increased, where the research that is reported in this article and whose purpose was to study the situation of educational units in the area Special Education and hearing impairment, in relation to written Spanish, to organize activities that encourage its use as a second language in children and young deaf people. For this, the method was the participant action investigation, it was based on a diagnosis of the situation, which gave account of the difficulties in the spontaneous relationship of the Deaf with the written code, therefore, the Language Olympiad for children and young people was planned deaf in the state of Aragua, its impact on the community was executed and evaluated. The Olympiad had as its main objective, to stimulate the use of texts written in Spanish by deaf children and young people; promote their participation in production activities and comprehension of written texts and LSV from different linguistic contexts. When evaluating the execution of the Olympiad, the active participation of deaf children and young people in the production of texts based on storytelling and storytelling was obtained; the understanding of narratives, expressed in written form, sign language and dramatization.